Confrontations of contingent workforce in Supeready industries: a case study. (2015) - Vihari, Nitin Simha; Rao, M.K.; Sathish, G.
In a challenging business environment, effective management of organisational workforce has been increasingly becoming a crucial competency and employee discipline as an overpass between organisational goals and accomplishments. In lieu of this, an instance of the same is observed and studied in Supeready industries, with special reference to its Chennai plant, which is primarily into manufacturing batteries and flashlights. As a market leader in its own segment, the manufacturing unit began to experience confrontation between the management and the hourly wage earners (HWEs), which had been consistently mediated by the union. As in every manufacturing company, HWEs in Supeready too shares a significant portion of the contingent workforce. For an illustrative and qualitative gap analysis, SAP-LAP framework was used as the key research method. The present case study results in academic and practitioner implications which special reference to the management of contingent workforce in the manufacturing sector.